+0  
 
0
65
1
avatar

Find the ordered pair, (s, t) that satisfies the system
(s/2) - 3t = -1,
3t - 2s = 3 + s - t

 Apr 13, 2022

Best Answer 

 #1
avatar+578 
+1

\(\begin{bmatrix}\left(\frac{s}{2}\right)-3t=-1\\ 3t-2s=3+s-t\end{bmatrix}\)

 

\(\mathrm{Substitute\:}s=-2+6t\)

 

\(\begin{bmatrix}3t-2\left(-2+6t\right)=3-2+6t-t\end{bmatrix}\)

 

\(\begin{bmatrix}-9t+4=5t+1\end{bmatrix}\)

 

\(t=3/14\)

 

\(\mathrm{Substitute\:} t\)

 

\(s=-2+6\cdot \frac{3}{14}\)

 

\(s=-5/7\)

 

\(=\)\((-5/7, 3/14)\)

 

smileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmiley

.
 Apr 13, 2022
 #1
avatar+578 
+1
Best Answer

\(\begin{bmatrix}\left(\frac{s}{2}\right)-3t=-1\\ 3t-2s=3+s-t\end{bmatrix}\)

 

\(\mathrm{Substitute\:}s=-2+6t\)

 

\(\begin{bmatrix}3t-2\left(-2+6t\right)=3-2+6t-t\end{bmatrix}\)

 

\(\begin{bmatrix}-9t+4=5t+1\end{bmatrix}\)

 

\(t=3/14\)

 

\(\mathrm{Substitute\:} t\)

 

\(s=-2+6\cdot \frac{3}{14}\)

 

\(s=-5/7\)

 

\(=\)\((-5/7, 3/14)\)

 

smileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmileysmiley

Vinculum Apr 13, 2022

20 Online Users